Mass Production of Sulfur‐Tuned Single‐Atom Catalysts for Zn–Air Batteries. Issue 15 (2nd March 2023) - Chen, Zehong; Peng, Xinwen; Chen, Zhongxin; Li, Tingzhen; Zou, Ren; Shi, Ge; Huang, Yongfa; Cui, Peng; Yu, Jian; Chen, Yuling; Chi, Xiao; Loh, Kian Ping; et al.
Abstract: Single‐atom catalysts (SACs) show great potential for rechargeable Zn–air batteries (ZABs); however, scalable production of SACs from sustainable resources is difficult owing to poor control of the local coordination environment. Herein, lignosulfonate, a by‐product of the papermaking industry, is utilized as a multifunctional bioligand for the mass production of SACs with highly active MN4 S sites (M represents Fe, Cu, and Co) via strong metalnitrogen/sulfur coordination. This effectively adjusts the charge distribution and promotes the catalytic performance, leading to highly durable and excellent performance in oxygen reduction and evolution reactions for ZABs. This study paves the way for the industrial production of cost‐effective SACs in a sustainable manner. Abstract : A single‐atom catalyst (SAC) with highly active MN4 S sites is successfully fabricated in a sustainable and large‐scale manner by utilizing a by‐product of the papermaking industry (i.e., lignosulfonate) as a multifunctional bioligand. The resulting SAC exhibits enhanced oxygen reduction and evolution reactions catalytic performance and shows high durability in Zn–air batteries.